Ceftolozane-Tazobatam for febrile neutropenia treatment in hematologic malignancy patients colonized by multi-resistant Enterobacteriaceae: preliminary results from a prospective cohort study - Francesco Marchesi; Luigi Toma; Enea Gino Di Domenico; Ilaria Cavallo; Antonio Spadea; Grazia Prignano; Fulvia Pimpinelli; Elena Papa; Irene Terrenato; Fabrizio Ensoli; Andrea Mengarelli (Mediterranean Journal of Hematology and Infectious Diseases)
NA